Challenges to the consolidation of pharmacovigilance practices in Brazil: limitations of the hospital pharmacist - Paulo Henrique Santos Andrade; Amanda Carvalho Barreiros de Almeida; Ana Keilla Santana dos Santos; Iza Maria Fraga Lobo; Francilene Amaral da Silva; Wellington Barros da Silva (SAGE Publishing, 2020)
Aims: The aim of this study was to present the needs of hospital pharmacists in pharmacovigilance practices. Methods: This study has a cross-sectional design and was carried out with hospital pharmacists in Brazil. The sample was obtained by voluntary recruitment. Pharmacists who worked at Brazilian hospitals and were registered in their respective regulatory councils were invited to participate in the present study. A personalized questionnaire was developed by the authors and was electronically filled out by the respondents on the platform 'Google forms'. The questionnaire was nationally available on the digital platform of the Pharmacy Federal Council, the Brazilian Society of Hospital Pharmacy and Health Services, four Pharmacy regional councils and the social network farmacêuticoclínico ® . Quantitative variables were analyzed by mean and standard deviation. The qualitative variables were analyzed by means of absolute and relative frequency. Difficulties related to pharmacovigilance activities are presented in an Ishikawa diagram in the Supplemental Material online. Results: Of the 27 federative units of Brazil, we obtained answers from pharmacists located in 85.2% ( n  = 23) of them. Among the pharmacovigilance practices developed by Brazilian pharmacists, the adverse drug reaction investigation (55.4%) and notification activities (47.0%) were worthy of note. Numerous difficulties were reported by the pharmacists, highlighting the difficulty in monitoring the medication and imputation of causality (27.7%). After categorizing the difficulties reported, it was observed that the category 'people involved' (45.1%) stood out from the others. Conclusion: This study pointed out numerous challenges to pharmacovigilance practices involving pharmacists in Brazil. It is believed that the correction of certain difficulties may impact on the better consolidation of pharmacovigilance activities in the country. However, regulatory agencies at all hierarchical levels of pharmacovigilance must work together to make it possible. Plain language Summary Challenges to the consolidation of pharmacovigilance This is a study that seeks to present the needs of Brazilian hospital pharmacists in relation to pharmacovigilance activities. Through online interviews, pharmacists answered a questionnaire, presented the pharmacovigilance activities they develop and expressed their anxieties and difficulties for the development of these activities. With this study, it was concluded that numerous activities of active search, investigation and notification of adverse drug reaction are developed by Brazilian pharmacists. However, each pharmacist performs a different method of pharmacovigilance. In addition, it was observed that among the interviewees there was a perception of insufficient professional training and a shortage of professionals to assist in pharmacovigilance activities. These were the main difficulties reported. Therefore, the search for models or agile solutions to solve problems involving adverse drug reactions seems necessary for a better consolidation of pharmacovigilance services in Brazil.